PENGARUH MOTIVASI BELAJAR, DISIPLIN BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP PRESTASI BELAJAR AKUNTANSI (Survey Pada Siswa Kelas XI IPS SMA Negeri 3 Palu) - Maryani, Maryani (Katalogis, 2016)
The purpose of this research is to analysis the influences of learning motivation, discipline and environment simultaneously toward student’s achievements on accountant. This research uses causal descriptive with the numbers of population were 170 students, this research used census technique sampling. Result of this research is to show the influences of learning motivation, discipline and environment simultaneously toward student’s achievement on accountant in eleventh grade students of SMA Negeri 3 Palu which is shown by double determination  adjustment coefficient  score ( Adj. R- Square (R) was 0,659.  This score shows that three independent variable in this research have big influences was 65,9% toward students achievement on accountant. While others was 34,1% has influenced by  other variable such as emotional question , spiritual question, culture and the leader style which wasn’t being observed but also give influence to students achievement on accountant  in SMA Negeri 3 Palu .